Using Benford’s law to detecting earnings management Application on a sample of listed companies in the Iraqi market for securities - يحيى عباس حميد; فليح حكيم حمود (Journal of Economics and Administrative Sciences, 2013)
Abstract The net profit reported in the annual financial statements of the companies listed in the financial markets, is considered one of the Sources of information relied upon by users of accounting information in making their investment decisions. At the same time be relied upon in calculating the bonus (Incentives) granted to management, therefore the management of companies to manipulate those numbers in order to increase those bonuses associated to earnings, This practices are called earnings management practices. the manipulation in the figures of earnings by management will mislead the users of financial statements who depend on reported earnings in their decisions. Because it did not honestly reflect the operational results of the companies, therefore are resorting to Benford’s Law is use to identify the companies that might be manage their earnings management , Where is this law is conceded one of the monitoring tools that have been used to detect the risk of earnings management , we Use Benford’s law to detect the companies that practiced earnings management in a sample of listed companies in the Iraqi stock exchange , The sample consisted of (61) companies from the (87) companies Listed on the market for the year 2010 , We concluded that there are a number of companies that practiced earnings management